봉와직염으로 오인된 슬개건내 결절성 통풍 - 임세혁(Se-Hyuk Im); 양보규(Bo-Kyu Yang); 남석우(Seok-Woo Nam); 정현석(Hyun-Seok Chung); 이승림(Seung-Rim Yi); 안영준(Young-Joon Ahn); 김성완(Seong-Wan Kim); 이예현(Ye-Hyun Lee) (The journal of the Korean Orthopaedic Association, 2015)
통풍은 관절의 급성 또는 만성 통증을 일으키는 흔한 원인 중의 하나로 요산 나트륨의 결정이 관절 주위 및 연부조직에 침착되어 일으키는 것으로 알려져 있다. 진단에 결정적인 요산 결절은 주로 족무지의 중족 족지 관절에서 시작되며 그 외에도 족근관절, 수근관절 등에도 침착 가능하다. 하지만 슬개건 내에 발생한 결절성 통풍에 대하여 국내에 보고된 경우는 없으며, 저자들은 봉와직염으로생각하고 며칠 간 항생제 치료를 시행한 뒤 증상의 호전이 없던 환자에 대해 자기 공명 영상 검사 후 슬개건 내에 자리잡은 낭종성 병변을 절개를 통해 육안적으로 통풍 결절을 관찰, 병리검사에서 확진한 경우를 증례보고하고자 한다. Gout is characterized by recurrent attacks of arthralgia, and deposition of monosodium urate crystals in and around the joints of the extremities and soft tissues. Monosodium urate crystals are observed most frequently at the 1st metatarsophalangeal joint and usually presented in the ankle and wrist joint. However, no case of an intratendinous tophus in the patellar tendon has been reported in Korean literature. In this report, we found monosodium urate crystals in the patellar tendon on magnetic resonance imaging images and intratendinous tophus were visible to the naked eye by excision. We reported on the case of a patient who experienced an unusual intratendinous tophus in the patellar tendon. KCI Citation Count: 0